2018
DOI: 10.1242/dev.158444
|View full text |Cite
|
Sign up to set email alerts
|

aPKC is a key polarity molecule coordinating the function of three distinct cell polarities during collective migration

Abstract: Apical-basal polarity is a hallmark of epithelia and needs to be remodeled when epithelial cells undergo morphogenetic cell movements. Here, we analyze border cells in the ovary to address how apical-basal polarity is remodeled and turned into front-back and inside-outside as well as apical-basal polarities, during collective migration. We find that the Crumbs (Crb) complex is required for the generation of the three distinct but interconnected cell polarities of border cells. Specifically, the Crb complex, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 44 publications
4
45
0
Order By: Relevance
“…As the epithelial walls touched, aPKC was specifically reduced at the contact point ( Figure 2B Remodeling of polarized epithelium is regulated by endosome recycling, where aPKC and cadherins are removed from the cell surface by endocytosis and shuttled to other membrane domains (Ivanov et al, 2004;Wang et al, 2018). Immunostaining for endosomal protein Rab11 revealed abundant apical puncta where the epithelium fuses in both Xenopus and in mouse, coincident with loss of aPKC and Cdh1 relocalization ( Figure 2E-F).…”
Section: Rab11 and Endosome-mediated Epithelial Remodeling Are Requirmentioning
confidence: 99%
“…As the epithelial walls touched, aPKC was specifically reduced at the contact point ( Figure 2B Remodeling of polarized epithelium is regulated by endosome recycling, where aPKC and cadherins are removed from the cell surface by endocytosis and shuttled to other membrane domains (Ivanov et al, 2004;Wang et al, 2018). Immunostaining for endosomal protein Rab11 revealed abundant apical puncta where the epithelium fuses in both Xenopus and in mouse, coincident with loss of aPKC and Cdh1 relocalization ( Figure 2E-F).…”
Section: Rab11 and Endosome-mediated Epithelial Remodeling Are Requirmentioning
confidence: 99%
“…Our data also support a role for Pp1 in controlling F-actin stability, dynamics, and spatial organization. Similar to the pattern of activated Myo-II, cortical F-actin is normally high at the cluster periphery, although low levels are found between border cells 23, 25, 61 . Reduced Pp1 activity causes high levels of F-actin to redistribute from the cluster perimeter to surround entire cell cortices of individual border cells.…”
Section: Discussionmentioning
confidence: 66%
“…The rounder cell shapes suggested that Pp1 inhibition alters the cortical cytoskeleton of the border cells. Wild-type border cells exhibit a marked enrichment of F-actin at the cluster periphery, whereas lower levels are detected inside the cluster at contacts between border cells (Figure 6D,D’,F; Video 11) 25, 61 . Upon Pp1 inhibition, F-actin now accumulated around each individual border cell, especially at BC-BC membrane contacts, rather than just being enriched at outer cluster surfaces (Figure 6E,E’,G; Video 12).…”
Section: Resultsmentioning
confidence: 97%
“…DE-Cad-GFP and DE-Cad-mCherry knock-in stocks were used as E-Cad reporters [49]. s lbo -GAL4, UAS-lifeact-GFP, UAS-LacZ stock was generously provided by Jiong Chen (Nanjing University) [92]. Fly stocks were raised on standard yeast-based media at 20°C, unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…Ectopic actin patch number was quantified as described [92]. Actin patch present at the base of the leading edge protrusion was excluded from quantification since it is not ectopic.…”
Section: Methodsmentioning
confidence: 99%